Invenções: arte africana - Macedo, Rafael Gonzaga de (2019)
What we call African art has delighted crowds since Eurocentric modernist artists and theorists, such as Picasso and Carl Einstein, chose it as a model for their aesthetic adventures and experiments. However, the displacement of these artifacts, such as masks and statuettes of orixás, which in their original context are worshiped in dark temples or religious festivals, to well-lit rooms of museums and art galleries was not a natural process or without contradictions. It is a cartography of African and black representations, and this mapping outlines, lines of escape and imagery that still haunts and haunted all those who once lived with these objects. From the romantic sublime of Frobenius, who saw in the art of Ife the remaining fruits of Atlantis; passing through the formalist look of Carl Einstein in the yearning for primitive vitality, the thesis flows into the childhood memories of the Bahian and black sculptor Agnaldo Manoel dos Santos in the 1940s. In this process, we will follow the long crossing marked by deaths, resistances and reinventions that gave the outlines for what we now call African art